How unemployment and precarious employment affect the health of young people: A scoping study on social determinants. Issue 1 (February 2017) - Vancea, Mihaela; Utzet, Mireia
Background: The impact of unemployment and precarious employment on the health of young people is not well understood. However, according to social causation, higher socio-economic positions and thus better working conditions are beneficial to health in general. We tried to synthesize the results of studies that test this hypothesis in the case of young people. Methods: We conducted a scoping study mapping all the academic articles published in the period 2006–2016 in Europe. The literature was searched in PubMed/Medline, Science Direct, Web of Science and Scopus. Results: We identified 1770 studies, of which only 46 met the inclusion criteria. There are more studies that focus on the relationship between unemployment and health than between precarious employment and health (28 and 16, respectively). The vast majority of the studies (44) found support for the social causation hypothesis, the most common health outcomes being mental health disorders, health risk behaviour, poor quality of life and occupational injuries. The causal mechanisms behind this association relied mainly on the life-course perspective, the breadwinner model, and the lack of social and economic benefits provided by standard employment. Conclusions: There is evidence that young people are especially vulnerable to health problems when unemployed or working in precarious conditions. Active labour market and training programmes, inclusive social security measures, improved working conditions and targeted health programmes are important for addressing this vulnerability. Further research should strive to enhance the causal model by including a gender perspective, longitudinal data, more indicators on precariousness and third factor explanations.